SiRiUS Stimulate Rice Ubiquitous System: AgWise integration - Aunario, Jorrel Khalil; Li, Tao; Quicho, Emma; Urfels, Anton (International Rice Research Institute, 2024)
Simulate Rice Ubiquitous System (SiRiUS) is an application for running small to large –scale ORYZA crop model simulations. It is fully open source and can be accessed at: https://github.com/jaunario/SiRiUS/. It leverages on freely available soil and weather data to estimate rice yield. This system is a powerful tool for fostering more sustainable, productive, and climate-resilient agricultural practices. As part of Excellence in Agronomy (EiA) – this efforts has been integrated for use in the AgWISE framework and can now be used for estimating spatial variations of optimal planting windows and potential yield of rice across geographies. Ongoing efforts are also using SIRIUS for estimating GHG emissions through IRRI’s Rice Computation Engine for GHG Emission (RiCEGEm) system.